On the Development of Two-Dimensional Wakes within Curved Channels: Experimental and Theoretical Investigation - M. T. Schobeiri; K. Pappu; J. John (International Journal of Rotating Machinery)
The development of a wake flow downstream of a cylindrical rod within a curved channel under zero streamwise pressure gradient is theoretically and experimentally investigated. The measured asymmetric wake quantities such as the mean velocity and turbulent fluctuations in longitudinal and lateral directions as well as the turbulent shear stress are transformed from the probe coordinate system into the curvilinear wake eigen-coordinate system. For the transformed nondimensionalized velocity defect and the turbulent quantities, affine profiles are observed throughout the flow regime. Based on these observations and using the transformed equations of motion and continuity, a theoretical framework is established that generally describes the two-dimensional curvilinear wake flow. The theory also describes the straight wake as a special case, for which the curvature radius approaches infinity. To demonstrate the general validity of theory, experimental results pertaining to curved wake as well as straight wake flows are compared with the developed theory.